The method of distant preconditioning and results of its application in renal transplantation from the living family donor - M. І. Kyrychenko; A. V. Bilyayev; N. G. Davydenko; A. O. Bychkova; O. V. Storozhuk (Клінічна хірургія, 2021)
Objective. Elaboration of method for the intraoperative ischemic-reperfusion trauma softening - distant ischemic preconditioning and investigation of results of its introduction into clinical practice.